PERAN SEKOLAH ISLAM DALAM PEMBENTUKAN KARAKTER SISWA DISEKOLAH ISLAM TERPADU HAJI JALALUDDIN - Gifra Gifra; Wedra Aprison (Institut Agama Islam Hamzanwadi NW Lombok Timur, 2024)
Islamic-based schools have an important role in efforts to instill religious values and shape student character to be better than before. The purpose of establishing an Islamic-based school is of course to produce students who are religious, disciplined, responsible, love the country, honest, independent, and care for others. Based on observations made by researchers at SDIT Haji Jalaluddin, it can be seen that the character of students cannot be said to be good because there are still many students who violate the rules at school. Thus, SDIT Haji Jalaluddin in addition to teaching religion in the classroom formally, the school also holds activities that support character building such as reading the Qur'an before learning, praying dhuha, holding zuhur congregational prayers, memorizing short letters and caring about the environment. The purpose of this study is to produce a description of the role of Islamic-based schools in the character building of SDIT Haji Jalaluddin students, as well as to find out the obstacles in the implementation of character building at SDIT Haji Jalaluddin.